Belarusian-Russian Relations and Their Influence on Belarusian Sovereignty - Zakrzewska, Sylwia Maria (The Copernicus Journal of Political Studies, 2018)
The evolution of the Belarusian-Russian relations in the course of the last several years and the integration processes that occurs between these states justify asking a question to what extent Belarus is an independent – sovereign – state. Author in this paper analysing economic and military the Belarusian-Russian cooperation and influence of this relation on Belarusian sovereignty. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762